O dwóch koncepcjach prawa naturalnego polskich filozofów prawa okresu międzywojennego - Szadok-Bratuń, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The first part of the article describes classification methods of the natural law concept in Polish philosophical and legal literature carried out based on the historical and systemic criteria. The first method allows analysing the ius naturale idea in its various cultural conditions at various stages of development of doctrines that the issue considers. The second method presents the phenomenon of natural law in the context of a comprehensive philosophical system. The Polish philosophical and legal thought has developed three systemic approaches to natural law: neo-Thomism in the style of the Lublin school of philosophy, psychologism by Leon Petrażycki and neo-Kantianism in the person of Maria Szyszkowska.The second part of the article is an attempt to investigate two types of opposing natural law concepts: epistemological in the style of an antipositivist, creator of legal politics and legal psychologism, L. Petrażycki and ontological presented by a neo-Thomist — Czesław Martyniak. Petrażycki’s natural law concept, which is a component of the psychological theory of law, was modified based on its three core elements: aspects of intuitive law, justice and legal politics. The importance of Petrażycki as the author of the term “revival of natural law” and creator of the theory of natural law of variable content was emphasised.The presentation of natural law views by C. Martyniak, that is the theory of natural laws of immutable content, is the author’s interpretation of natural law by St. Thomas of Aquinas made in the spirit of the Thomistic school of philosophy of law. Martyniak, apart from translating the Aquinas’ treatise on law contained in the Theological Summa, conducted a critical analysis of the definition, content and properties of natural law, which on a large scale appeared only in the post-conciliar current. He was the only representative of the philosophy of law in the interwar period who went in for it in the context of Thomas’ science and the first scholar who gave regular lectures on the philosophy of law at the Catholic University of Lublin.
Keywords: prawo naturalne; polscy filozofowie prawa; koncepcje; okres międzywojenny